Composition and physicochemical properties of colostrum and transient milk of Landrace, Large White, and their F1 crosses in a swine breeding farm in Laguna, Philippines - Bondoc, Orville L.; Isubol, Joemary F.; Ebron, Aldrin O.; Rama, Adonna Jane C. (2020)
This study evaluated the composition (% moisture, % protein, % fat, % solids non-fat or SNF) and physicochemical properties (density, specific gravity, freezing temperature, conductivity) of colostrum and transient milk obtained from Landrace, Large White, and their F1 crosses in a swine breeding farm in Laguna, Philippines. Composition and physicochemical properties of sow?s milk were invariably affected by the type of milk, sow breed, month of farrowing, and parity. Colostrum had significantly (P < 0.01) higher % protein (9.19 ± 0.43% vs. 6.89 ± 0.51%), % SNF (19.11 ± 0.80% vs. 14.58 ± 0.94%), density (75.66 ± 6.65 g/mL vs. 52.63 ± 6.97 g/mL) and specific gravity (1.070 ± 0.003 g/cm3 vs. 1.050 ± 0.004 g/cm3), but lower % moisture (73.85 ± 0.93% vs. 77.77 ± 1.09%) and conductivity (2.95 ± 0.13 mS/cm vs. 3.62 ± 0.15 mS/cm) than transient milk. Both the density and specific gravity of colostrum were negatively correlated with pre-weaning mortality (r = ?0.30). Parity was negatively correlated with %protein (r = ?0.41), % solids non-fat (r = ?0.38), density (r = ?0.36), and specific gravity (r = ?0.36) of transient milk. The composition and physicochemical properties of colostrum were not significantly different (P > 0.05) between pure Landrace and Large White. For transient milk, however, Landrace had significantly (P < 0.05) higher % protein, density, and specific gravity but lower % moisture than Large White. ?R1 Large White x Landrace? had significantly (P<0.05) higher density and specific gravity of colostrum than ?F1 Landrace x Large White?. For transient milk, however, ?R1 Large White x Landrace? had significantly (P < 0.05) higher % moisture but lower % protein, % SNF, and specific gravity than ?F1 Landrace x Large White?. As % moisture generally decreases and % fat increases from May?September 2019, % moisture in transient milk was significantly higher (P < 0.01) than in colostrum in sows farrowing from May?July only. Percent fat in transient milk was significantly higher (P < 0.01) than in colostrum in August only. Local pig producers may use these observations in their management to attain the desired composition and quality of colostrum and transient milk. (Author's abstract)